The classification and therapeutic applications of molecular motors - Mingyuan Li; Yuan Li; Lin Jia; Shiqin Li; Meng Li; Guang Yang; Nan Liu; Hongmeng Ren; Mingqi Mou; Aiping Zheng; Hua Sun (Elsevier, 2021)
The molecular motors are protein molecules which can be teamed up to form the active mobile nanomachine with special functions. As a new type of therapeutic target different from normal enzymes or receptors, molecular motor plays a unique role in the transportation of intracellular substances, mitosis, and the construction of cytoskeleton. It has also been reported that molecular motors were capable of regulate the tumor cells' proliferation, related to the occurrence of neurodegenerative diseases, and can be used as a nano carrier to deliver drugs. Molecular motors could be divided into linear and rotary molecular motors according to their different forms of motion. The former includes dynein, kinesin, and myosin, and the latter includes ATP synthase and flagellar motors. In addition, there are also some chemically or biologically modified molecular motors to expand or enhance their therapeutic applications. In this review, after the introduction of the classification, structures, main functions and motion mechanism of molecular motors in detail, the application progress of molecular motors in recent years is summarized. Finally, the current problems and future prospect are also discussed in this paper.